Medical Waste Storage Practice in Health Care Institutions of Pokhara Sub-metropolitan City - Baral, Prakash; Banstola, R; Nepal, D; Baral, P (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: Medical wastes include all the waste generated by health care establishments, research facilities, and laboratories. Medical waste is any waste that is generated in the diagnosis, treatment or immunization of human beings or animals, in research pertaining there to or in the productions or testing of biological culture. Methods: The fourteen numbers of health care institutions (HCIs) having inpatient facilities, were sampled for the study. After taking observation, the collected information was entered into a computer. Basically, the percentages, projection analysis, simple average, and scenario analysis were used as an analysis tools. Results: Out of the HCIs surveyed, only 21.43% of them had a separate room assigned for primary storage of all sorts of waste and remaining 78.57% of them had open storage facilities for un-segregated mass of waste nearby the incineration area or open burning area. Conclusion: There was lack of appropriate information on waste storage practices, and unaware of designing central storage system in HCIs. In most of the HCIs, a separate storage room was not assigned for storage of all sorts of waste. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, page: 31-33